Pengaruh Rasio Profitabilitas Likuiditas Dan Aktivitas Terhadap Nilai Perusahaan - Sari, Maya; Ilmi, Nurul (Jurnal Riset AKuntansi dan Bisnis, 2024)
The development of a company cannot be separated from the role of financial reports. Financial reports are not only limited to testing tools, but can also be a basis for decision making. This research aims to determine the influence of profitability, liquidity and activity ratios on company value at PT. Japfa Comfeed Indonesia Tbk. This type of research uses Quantitative research; Secondary Data sampling technique; data collection techniques using documentation methods; The data analysis technique used in the research uses the analysis tools of the Statistical Package For Social Science (SPSS26) program. Based on partial research results, it was found that the Profitability Ratio which was proxied by Return On Assets (ROA) and the Activity Ratio which was proxied by Total Asset Turnover (TATO) had a significant effect on company value while the Liquidity Ratio which was proxied by the Current Ratio (CR) had no significant effect. significant to company value. Based on the F test, it can be concluded that simultaneously Return On Assets (ROA), Current Ratio (CR) and Total Asset Turnover (TATO) have a significant effect on company value..